Purchase of food by ecommerce in Costa Rica during COVID-19 - Villalobos Monge, Alexis (2022)
Introduction. The influence of electronic commerce (EC) on people’s food purchasing decisions has been relevant during the COVID-19 pandemic. In Costa Rica, there is no information available on how this medium has modified the food purchasing and consumption behaviors in Costa Rican families during this health emergency. Objective. To analyze changes in the food purchase and consumption patterns of Costa Ricans that were influenced by the EC during the pandemic. Materials and methods. An online survey using the snowball methodology was carried out in June 2021 in different social networks groups in Costa Rica. Structural equation modeling was used to establish the causes associated with endogenous (trust, convenience, hedonic impulses) and exogenous variables (socioeconomic status, purchase decisions due to COVID-19) that outlined the changes in purchasing habits. The stimuli generated from EC that influenced these purchase decisions were reviewed according to the specific food group. Results. A strong causality was found from the latent variable convenience (β=0.89; p<0.01) for the purchase of food by EC, in addition to little impact (β=-0.35; p<0.01) on food consumption habits, generated by the measures defined to contain the pandemic. The sanitary measures established by the authorities show causality in the general response of the food consumer by EC (NORM_1<0.8; p<0.01), which was low if its estimated value is compared with other motivators in purchase decisions such as convenience due to improvements in quality of life (CO1@0.8; p<0.01) or even trust due to the commitment to quality offered by the website (CF3@0.6; p<0.01). Conclusions. The pandemic promoted an improvement in consumer perception regarding advantageous situations of employing EC to make food purchases.